Correlation of CA-125 value and histological finding of adnexal mass in a Cancer Hospital (Nepalese Journal of Cancer, 2026)
Background: To predict the nature of the adnexal mass, CA-125 is commonly used as a tumor marker. The diagnostic and prognostic value depends on the serum value of CA-125 and the histological variant. This study aims to determine the correlation between serum CA-125 levels and histopathological findings in adnexal masses.Methods: This retrospective study was conducted at a tertiary care cancer hospital. Medical records of patients who underwent surgery for adnexal masses were reviewed. Preoperative serum CA-125 values were categorized into five ranges: